A rapid and efficient DNA extraction method from high oily content seeds: Ricinus communis L.- apt for PCR based assay - Elham R. S. SOLIMAN (Acta Agriculturae Slovenica, 2023)
Ricinus communis seeds harbor high oil and polyphenolics contents that hinder DNA extraction. Here, a rapid and efficient protocol for isolating total DNA from R. communis seeds was developed. The current method implies the use of repeated cycles of freeze/heat shock for the seed tissue to lyse the cells. DNA isolated with this protocol was successfully used as a template for PCR amplification of the internal transcribed spacer (ITS) region of the rRNA encoding gene that widely used for molecular identification of different plant species. As far to our knowledge, this study is the first one that report the efficient use of freeze/heat shock repeated cycles for isolation of a high-quality DNA from plant cells. The current protocol would support the subsequent analysis for seed lot purity analysis.